(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
This work aims to analyze the relationship between value added tax (VAT) and economic growth in China and Mexico for the period 1991-2021. This research uses the gross domestic product (GDP) as the dependent variable, for the independent variables this research uses VAT and tax revenue. The test results indicated that for China there is a strong and positive relationship between GDP and VAT, as for Mexico the relationship although positive is not strong.